Pendampingan Optimalisasi Pemanfaatan Daun Kelor Sebagai Pangan Tambahan di Desa Randuputih - Gustav Ahmadi; Thariq Zinedin Widiansyah; Linc Bellatrix Adhara; Kustini Kustini; Zainal Abidin Achmad; Dita Atasa (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
The activity of optimizing the utilization of moringa leaves as an additional food source in Randuputih Village has become a strategic solution to improve the nutritional status of the community, reduce the incidence of stunting, and alleviate hunger in support of achieving Sustainable Development Goal (SDG) 2. This initiative is carried out by students from the Community Service Program (KKNT) Group 1 at UPN "Veteran" East Java, Field Supervisors (DPL), and in collaboration with the National Population and Family Planning Board (BKKBN) of East Java Province. The target of the activity is 25 households participating in the Posyandu (integrated health post) in Randuputih Village. The form of optimizing the utilization of moringa leaves includes enhancing moringa production, disseminating information about the benefits of moringa leaves, and promoting the consumption of diverse, nutritious, balanced, and safe food (B2SA). Based on the mentoring results, there was a 50% increase in the knowledge of the participating mothers. Through these outcomes, it is expected that the mothers in Randuputih Village can apply the knowledge gained to improve nutritional status and reduce the incidence of stunting in the community.